Birth dearth and local population decline - Brian J. Asquith; Evan Mast (W.E. Upjohn Institute for Employment Research, 2024)
Local population decline has spread rapidly since 1970, with half of counties losing population between 2010 and 2020. The workhorse economic models point to net out-migration, likely driven by changing local economies and amenities, as the cause of this trend. However, we show that the share of counties with high net out-migration has not increased. Instead, falling fertility has caused migration rates that used to generate growth to instead result in decline. When we simulate county populations from 1970 to the present holding fertility at its initial level, only 10 percent of counties decline during the 2010s.
Keywords: J11; J13; N92; R11; 330; fertility; population decline; migration; counties; simulations